Diversity of macrofungi in UiTM Forest Reserve, Kuala Pilah, Negeri Sembilan / Nur Ain Liyana Mustapha and Ahmad Zaimi Mohd Zawawi - Mustapha, Nur Ain Liyana; Mohd Zawawi, Ahmad Zaimi (UiTM Cawangan Negeri Sembilan, 2022)
Macrofungi have perhaps the longest history of diversity studies, yet they are understudied over most of the world. They perform some of the significant parts in life and also have advantages for biotechnology, nevertheless only 7% of the total estimated fungal species are reported worldwide. The diversity of fungi is greatly influenced by biotic and abiotic factors. Different families and species have different nutritional modes and are associated with substrates that offer a preferable condition to grow. In UiTM Forest Reserve, Kuala Pilah, Negeri Sembilan, the diversity of macrofungi is poorly documented and unexplored taxonomic diversity resulted in a lack of awareness of their importance in the ecosystem. Thus, this study aimed to identify families, genera and to determine the diversity of macrofungi in the UiTM Forest Reserve. This study may gain knowledge about the diversity of macrofungi that has been recorded in this area and contribute towards conservation together with preservation efforts on ecosystem health and forest resources as a need for sustainable development. The sampling activity was conducted four times in April 2021 and the samples were photographed before being recorded based on morphological features. The specimens were placed into ziplock bags separately then were brought to the laboratory for the identification process. In total, five orders and ten families were identified from 160 samples collected. The highest number of fruiting bodies contributed by Agaricales by 81 from six families and 15 species, followed by Polyporales, Auriculariales, Hymenochaetales and Hypocreales with 57, 17, 4 and 1 fruiting bodies respectively. The statistical analysis shown the diversity (H) = 2.54, evenness (E) = 0.58 and richness (R) = 4.14 of macrofungi diversity respectively. UiTM Forest Reserve thus has high macrofungi diversity. However, further thorough studies are required to document more on macrofungi diversity within this area.